Goddess girls. 3, Aphrodite the beauty - Holub, Joan; Campiti, David; Williams, Suzanne, 1953- (Campiti, David. Goddess girls graphic novel, 2022)
Aphrodite, goddess girl of love, must deal with jealousy after giving Athena a makeover. It doesn't seem fair that the god boys pay more attention to her friend when Aphrodite is supposed to be destined for love! She also copes with a crush from an unlikely source--the nerdy Hephaestus (god of the smith)--and learns that love comes in many forms.